Customized mandibular reconstruction plates improve mechanical performance in a mandibular reconstruction model. Issue 4 (12th March 2017) - Gutwald, Ralf; Jaeger, Raimund; Lambers, Floor M.
Abstract: The purpose of this paper was to analyze the biomechanical performance of customized mandibular reconstruction plates with optimized strength. The best locations for increasing bar widths were determined with a sensitivity analysis. Standard and customized plates were mounted on mandible models and mechanically tested. Maximum stress in the plate could be reduced from 573 to 393 MPa (−31%) by increasing bar widths. The median fatigue limit was significantly greater ( p < 0.001) for customized plates (650 ± 27 N) than for standard plates (475 ± 27 N). Increasing bar widths at case-specific locations was an effective strategy for increasing plate fatigue performance.